ICT Innovations 2015 Emerging Technologies for Better Living - Loshkovska, Suzana; Koceski, Saso (Advances in Intelligent Systems and Computing, 2016)
This book offers a collection of selected papers presented at the Seventh International Conference on ICT Innovations held in October 2015, in Ohrid, Macedonia, with main topic Emerging Technologies for Better Living. The conference gathered academics, professionals and industrial practitioners that work on developing the emerging technologies, systems, applications in the industrial and business arena especially innovative commercial implementations, novel application of technology, and experience in applying recent ICT research advances to practical solutions.